2022
DOI: 10.1146/annurev-matsci-081720-105303
|View full text |Cite
|
Sign up to set email alerts
|

Biomineralized Materials for Sustainable and Durable Construction

Abstract: Portland cement concrete, the most used manufactured material in the world, is a significant contributor to anthropogenic carbon dioxide (CO2) emissions. While strategies such as point-source CO2 capture, renewable fuels, alternative cements, and supplementary cementitious materials can yield substantial reductions in cement-related CO2 emissions, emerging biocement technologies based on the mechanisms of microbial biomineralization have the potential to radically transform the industry. In this work, we prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 151 publications
0
11
0
Order By: Relevance
“…Recently, photosynthetic MICP performed by cyanobacteria has received more attention in several engineering approaches because they serve as a carbon capture system by absorbing CO 2 during growth and mineralization ( Heveran et al, 2020 ; Beatty et al, 2022 ; Sidhu et al, 2022 ). Heveran et al (2020) investigated the inclusion of mineralizing cyanobacteria in a gelatin-hydroge-sand mixture by gel casting and demonstrated promising results in terms of the creation of consolidated constructs, probably caused by cyanobacteria-induced CaCO 3 mineralization, which improved the mechanical properties of such building materials.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, photosynthetic MICP performed by cyanobacteria has received more attention in several engineering approaches because they serve as a carbon capture system by absorbing CO 2 during growth and mineralization ( Heveran et al, 2020 ; Beatty et al, 2022 ; Sidhu et al, 2022 ). Heveran et al (2020) investigated the inclusion of mineralizing cyanobacteria in a gelatin-hydroge-sand mixture by gel casting and demonstrated promising results in terms of the creation of consolidated constructs, probably caused by cyanobacteria-induced CaCO 3 mineralization, which improved the mechanical properties of such building materials.…”
Section: Introductionmentioning
confidence: 99%
“…In other work, calcium carbonate precipitated in the presence of high organic content produces smaller and much less stiff crystals 11,36 . Our work adds to a growing body of research demonstrating that calcium carbonate produced in association with ureolytic microorganisms or enzymes varies considerably in morphology and material properties and extends these findings into the fungal kingdom 2,4,8,9,12,15,21,37,39 . These data also suggest that there is a large design space available for tailoring the growth and biomineral characteristics of biomineralized fungal scaffolds.…”
Section: Discussionmentioning
confidence: 55%
“…Fungal mycelium could also be utilized to biomineralize the ELM. Previously, biomineralized ELMs have been stiffened by bacterial biomineralization 5, 8, 11, 12, 14, 16, 3638 . The most common metabolism employed in these types of materials is urea hydrolysis, facilitated by the production of the urease enzyme by bacterial species such as Sporosarcina pasteurii 11, 15, 39 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the SPCF has excellent cooling performance on the wooden buildin which applies not only to the hot sunny days but also to the hot overcast days. Cement is a commonly used material for the building exterior wall, and if the SPC covers on the cement in the hot summer, it is possible to achieve temperature regulatio without energy consumption by a simple operation [42,43]. The schematic diagram of th experimental setup is shown in Figure 4a.…”
Section: Cooling Performance Of the Spcf On The Building Model And Th...mentioning
confidence: 99%
“…It can be concluded that even with the cemen which is a practical building material, the SPCF still shows excellent cooling performanc which is important for achieving passive cooling in practical buildings. Cement is a commonly used material for the building exterior wall, and if the SPCF covers on the cement in the hot summer, it is possible to achieve temperature regulation without energy consumption by a simple operation [42,43]. The schematic diagram of the experimental setup is shown in Figure 4a.…”
Section: Cooling Performance Of the Spcf On The Building Model And Th...mentioning
confidence: 99%